polycondensate

The new Bechulin polyurethane material is formed by reacting Bechulin with aliphatic isocyanate, which solves the problem of insufficient application of Bechulin and achieves a soft material with high solubility and wide-band vibration suppression.

JP2025017227APending Publication Date: 2025-02-05YAMAHA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023120227
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-02-05

Smart Images

  • Figure 2025017227000006
    Figure 2025017227000006
  • Figure 2025017227000007
    Figure 2025017227000007
  • Figure 2025017227000008
    Figure 2025017227000008
Patent Text Reader

Abstract

To provide a novel polycondensate comprising betuline.SOLUTION: The present invention provides a polycondensate of betuline and aliphatic diisocyanate, wherein, the peak integral value in the chemical shift range of 3.10-3.20 ppm in the 1H-NMR spectrum is more than 2.0, assuming that the peak integral value in the chemical shift range of 2.30-2.55 ppm is 1.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polycondensate. [Background technology]

[0002] Betulin, which is found in the outer bark of white birch, is one of the renewable natural materials that effectively utilize plants, and is an excellent material with characteristics such as heat resistance, ultraviolet absorption properties, ultraviolet resistance properties, antibacterial properties, etc. In the field of betulin research, much research has been conducted on methods for extracting and refining from white birch bark, betulin itself, betulin derivatives, and polymers that use betulin.

[0003] For example, Japanese Patent Application Laid-Open No. 2001-288222 describes the production of a polymer having an average molecular weight of 50,000 by reacting betulin with hexamethylene diisocyanate at 50° C. for 24 hours in a nitrogen atmosphere. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2001-288222 A Summary of the Invention [Problem to be solved by the invention]

[0005] The problem to be solved by the present invention is to provide a novel polycondensate using betulin. [Means for solving the problem]

[0006] The means for solving the above problems is a polycondensation product of betulin and an aliphatic diisocyanate, 1 The polycondensate has a peak integral value of more than 2.0 in a chemical shift range of 3.10 to 3.20 ppm when the peak integral value in a chemical shift range of 2.30 to 2.55 ppm in a H-NMR spectrum is taken as 1. Effect of the Invention

[0007] The effect of the present invention is to provide a novel polycondensate using betulin. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is an IR measurement chart of the polycondensate (A-1). [Diagram 2] FIG. 2 is an IR measurement chart of the polycondensate (A-15). [Diagram 3] FIG. 3 is an IR measurement chart of the polycondensate (A-16). [Figure 4] FIG. 4 is an IR measurement chart of the polycondensate (A-17). [Diagram 5] FIG. 5 is a 1H-NMR measurement chart of the polycondensate (A-1). [Figure 6] FIG. 6 is a 1H-NMR measurement chart of the polycondensate (A-15). [Figure 7] FIG. 7 is a 1H-NMR measurement chart of the polycondensate (A-16). [Figure 8] FIG. 8 is a 1H-NMR measurement chart of the polycondensate (A-17). [Figure 9] FIG. 9 shows the results of DSC measurement of the polycondensate (A-1). [Figure 10] FIG. 10 is an enlarged view of the results of DSC measurement of the polycondensate (A-1). [Figure 11] FIG. 11 shows the results of DSC measurement of the polycondensate (A-16). [Figure 12] FIG. 12 is an enlarged view of the results of DSC measurement of the polycondensate (A-16). [Figure 13] FIG. 13 shows the results of DSC measurement of the polycondensate (A-17). [Figure 14] FIG. 14 is an enlarged view of the results of DSC measurement of the polycondensate (A-17). [Figure 15] FIG. 15 shows the results of TG-MS measurement of the polycondensate (A-1). [Figure 16] FIG. 16 shows the results of Tg measurement of the polycondensate (A-1). [Figure 17] FIG. 17 shows the results of Tg measurement of the polycondensate (A-16). [Figure 18] FIG. 18 shows the results of Tg measurement of the polycondensate (A-17). [Figure 19] FIG. 19 shows the results of measuring the specific elastic modulus. [Figure 20] FIG. 20 shows the measurement results of the loss tangent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described.

[0010] In this specification, the numerical range described using "~" includes the numerical values ​​before and after "~" as the lower and upper limits. Unless otherwise specified, the description of the upper and lower limits of the numerical range in this specification may mean "less than or equal to" or "less than," and the lower limit may mean "more than or equal to" or "greater than."

[0011] <Polycondensation product> The polycondensate is a polycondensate of betulin and an aliphatic diisocyanate. That is, the polycondensate has a structural unit derived from betulin (hereinafter also referred to as "structural unit (I)") and a structural unit derived from an aliphatic diisocyanate (hereinafter also referred to as "structural unit (II)"). In the polycondensate, a combination of the structural unit (I) and the structural unit (II) is called a unit. The polycondensate may have structural units other than the structural unit (I) and the structural unit (II) within a range that does not impair the effects of the present invention.

[0012] The polycondensate is 1The peak integral value in the chemical shift range of 3.10 to 3.20 ppm is more than 2.0 when the peak integral value in the chemical shift range of 2.30 to 2.55 ppm in the H-NMR spectrum is set to 1. Theoretically, in the polycondensation product of betulin and aliphatic diisocyanate, the theoretical value of the peak integral value in the chemical shift range of 3.10 to 3.20 ppm is 2.0 when the peak integral value in the chemical shift range of 2.30 to 2.55 ppm is set to 1. The peak in the chemical shift range of 3.10 to 3.20 ppm is assigned to the proton of the urethane bond (-NH-CO-). The polycondensation product can be said to be a novel betulin polyurethane because the peak integral value in the chemical shift range of 3.10 to 3.20 ppm is more than 2.0.

[0013] The lower limit of the peak integral value in the chemical shift range of 3.10 to 3.20 ppm is preferably 3.0, more preferably 3.5, further preferably 4.0, and even more preferably 4.2. The upper limit of the peak integral value is preferably 5.0, and more preferably 4.8.

[0014] 1 The integral value of each peak in the H-NMR spectrum was measured using a nuclear magnetic resonance apparatus (JNM-ECX400 manufactured by JEOL Ltd.) under the conditions of solvent: CDCl3, internal standard: tetramethylsilane.

[0015] The lower limit of the weight average molecular weight (Mw) of the polycondensate is preferably 3,000, more preferably 4,000, even more preferably 5,000, and even more preferably 6,000. The upper limit of the Mw is preferably 30,000, more preferably 20,000, even more preferably 15,000, and even more preferably 7,500. In general, polyurethane is known to have poor solubility in solvents, but when the Mw is equal to or less than the upper limit, the solubility of the polycondensate in solvents can be increased. More specifically, when the Mw is equal to or less than 30,000, the solubility in solvents is improved, and as a result, the range of application of the polycondensate is expected to be expanded.

[0016] The lower limit of the polydispersity (Mw / Mn) of the polycondensate is preferably 1.0. The upper limit of the Mw / Mn is preferably 15.0, more preferably 10.0, further preferably 6.0, even more preferably 5.0, and particularly preferably 4.0.

[0017] In this specification, Mw and Mn are values ​​measured by gel permeation chromatography (GPC) using Showa Denko K.K.'s "SHODEX GPC-104," GPC columns: Showa Denko K.K.'s "KF802," one column, "KF803," and one column, "KF804," eluent: tetrahydrofuran, column temperature: 40° C., flow rate: 0.3 mL / min, sample concentration: 0.1 to 0.2 mass%, sample injection amount: 0.75 mL, detector: differential refractometer, standard substance: monodisperse polystyrene.

[0018] The polycondensate has a lower specific modulus and loss tangent (tan δ) than conventional rigid polyurethane foams. Also, the polycondensate has a lower specific modulus and a higher loss tangent (tan δ) than various diaphragm materials. Therefore, the polycondensate is useful as an acoustic material for high frequencies. For example, it is useful as a soft material for wide frequencies that suppresses split vibrations.

[0019] Each structural unit and unit contained in the polycondensate will be described below.

[0020] Structural Units The structural unit (I) is a structural unit derived from betulin and is represented, for example, by the following formula (1).

[0021] [ka]

[0022] In the above formula (1), * indicates the site at which the structural unit (I) bonds to the structural unit adjacent thereto.

[0023] The lower limit of the content of the structural unit (I) is preferably 30 mol%, more preferably 40 mol%, and even more preferably 48 mol%, based on the total structural units constituting the polycondensate.The upper limit of the content is preferably 70 mol%, more preferably 60 mol%, and even more preferably 52 mol%.

[0024] [Structural unit (II)] The structural unit (II) is a structural unit derived from an aliphatic diisocyanate. The structural unit (II) is represented, for example, by the following formula (2). The polycondensate may have one or more types of structural units (II).

[0025] [ka]

[0026] In the above formula (2), R is a substituted or unsubstituted divalent aliphatic hydrocarbon group having 1 to 20 carbon atoms. * indicates the bonding site to the structural unit adjacent to the structural unit (II).

[0027] Examples of the divalent aliphatic hydrocarbon group having 1 to 20 carbon atoms represented by R include alkanediyl groups, such as a methanediyl group, an ethanediyl group, a propanediyl group, a butanediyl group, a pentanediyl group, a hexanediyl group, a heptanediyl group, an octanediyl group, a nonanediyl group, a decanediyl group, a dodecanediyl group, a tetradecanediyl group, a hexadecanediyl group, an octadecanediyl group, or an icosanediyl group; Alkenediyl groups such as an ethenediyl group, a butenediyl group, a hexenediyl group, or an octenediyl group; Chain hydrocarbon groups having 1 to 20 carbon atoms, such as alkynediyl groups, such as ethynediyl groups, butynediyl groups, hexynediyl groups, and ocynediyl groups; cycloalkanediyl groups such as a cyclopropanediyl group, a cyclopentanediyl group, a cyclohexanediyl group, a cyclooctanediyl group, or a methanediylcyclohexanediylmethanediyl group; Examples of the alicyclic hydrocarbon group include cycloalkenediyl groups having 3 to 20 carbon atoms, such as a cyclopropenediyl group and a cyclohexenediyl group.

[0028] The aliphatic hydrocarbon group is preferably a chain hydrocarbon group, more preferably an alkanediyl group.

[0029] The lower limit of the number of carbon atoms in the aliphatic hydrocarbon group is preferably 6, and more preferably 7. The upper limit of the number of carbon atoms is preferably 16, and more preferably 14, and even more preferably 12.

[0030] Examples of the substituent that the aliphatic hydrocarbon group may have include halogen atoms such as a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom, a hydroxyl group, a carboxyl group, a cyano group, and a nitro group.

[0031] The aliphatic hydrocarbon group is preferably unsubstituted. By using an unsubstituted aliphatic hydrocarbon group, the reactivity of the aliphatic diisocyanate in polycondensation can be further increased.

[0032] Examples of the aliphatic diisocyanate which provides the structural unit (II) include 1,4-diisocyanate butane, 1,6-diisocyanate hexane, 1,8-diisocyanate octane, and 1,12-diisocyanate dodecane.

[0033] The lower limit of the number of carbon atoms excluding the isocyanate group of the aliphatic diisocyanate is preferably 6, and more preferably 7. The upper limit of the number of carbon atoms is preferably 16, and more preferably 14, and even more preferably 12.

[0034] The lower limit of the content of the structural unit (II) is preferably 30 mol%, more preferably 40 mol%, and even more preferably 48 mol%, based on the total structural units constituting the polycondensate.The upper limit of the content is preferably 70 mol%, more preferably 60 mol%, and even more preferably 52 mol%.

[0035] [unit] An example of the unit contained in the polycondensate is a unit represented by the following formula (3).

[0036] [ka] In the above formula (3), R has the same meaning as in the above formula (2).

[0037] It is strongly suggested that water exists in the vicinity of the urethane bond in the polycondensate. Therefore, the polycondensate is considered to have a structure represented by the following formula (4).

[0038] [ka]

[0039] In the above formula (4), R has the same meaning as in the above formula (2).

[0040] [Other structural units] Examples of other structural units include structural units derived from diols other than the structural unit (I), structural units derived from aromatic diisocyanates other than the structural unit (II), and the like.

[0041] Examples of the diol include aliphatic diols such as ethylene glycol, propylene glycol, 1,6-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, and cyclohexanedimethanol, and aromatic diols such as benzenedimethanol.

[0042] Examples of the aromatic diisocyanate include diphenylmethane diisocyanate and toluene diisocyanate.

[0043] The polycondensate preferably contains no other structural units than the structural units (I) and (II).

[0044] <Method of producing polycondensate> The method for producing the polycondensate includes a step of reacting betulin with an aliphatic diisocyanate in a solvent (hereinafter also referred to as the "reaction step"), and a step of introducing the reaction product obtained by the reaction step into water (hereinafter also referred to as the "precipitation step").

[0045] The method for producing the polycondensate includes the reaction step and the precipitation step, and thereby the above-mentioned polycondensate can be produced.

[0046] Each step of the method for producing the polycondensate will be described below.

[0047] [Reaction process] In this process, betulin and an aliphatic diisocyanate are reacted in a solvent. Usually, betulin is a powdery solid. For example, when powdery betulin and liquid aliphatic diisocyanate are mixed, the liquid aliphatic diisocyanate is absorbed by the powdery betulin, resulting in a non-uniform state. In a non-uniform state, there is a risk of problems such as insufficient progress of the polycondensation reaction or undesired side reactions proceeding. Therefore, in this process, it is believed that the polycondensation reaction between betulin and an aliphatic diisocyanate can be efficiently progressed by carrying out the reaction in a solvent. It is also believed that the polycondensation product can be obtained in a good yield by carrying out the reaction in a solvent.

[0048] The lower limit of the amount of the aliphatic diisocyanate used is preferably 0.5 times by mole, more preferably 0.8 times by mole, relative to betulin, and the upper limit of the amount used is preferably 1.5 times by mole, more preferably 1.2 times by mole.

[0049] Examples of the solvent include Ethers such as diethyl ether, dipropyl ether, butyl methyl ether, tert-butyl methyl ether, dibutyl ether, ethyl phenyl ether, diphenyl ether, tetrahydrofuran (THF), 1,4-dioxane, etc.; Alcohols such as methanol, ethanol, isopropyl alcohol, isobutyl alcohol, isopentyl alcohol, neopentyl alcohol, etc.; Ketones such as acetone, ethyl methyl ketone, methyl propyl ketone, diethyl ketone, ethyl propyl ketone, and dipropyl ketone; Halogenated hydrocarbons such as methylene chloride, chloroform, carbon tetrachloride, 1,2-dichloroethane, 1,1-dichloroethane, trichloroethane, and chlorobenzene; Nitriles such as acetonitrile, propionitrile, benzonitrile, etc.; Aliphatic hydrocarbons such as heptane, pentane, hexane, octane, cyclohexane, etc.; Examples of the aromatic hydrocarbons include benzene, toluene, xylene, mesitylene, and ethylbenzene.

[0050] As the solvent, from the viewpoint of the solubility of the polycondensate, ether is preferable, and THF is more preferable. The solvent used in the reaction may be one or more kinds.

[0051] This step can be carried out, for example, by adding an aliphatic diisocyanate to a solution in which betulin is dissolved in a solvent.

[0052] The lower limit of the betulin concentration in the reaction solution at the start of this process is preferably 10 mM, more preferably 50 mM, and even more preferably 150 mM. The upper limit of the betulin concentration is preferably 1,000 mM, more preferably 500 mM, even more preferably 350 mM, and even more preferably 280 mM. In particular, when the betulin concentration in the reaction solution at the start of this process is within the above range, the yield of the polycondensate can be improved.

[0053] The lower limit of the reaction temperature is preferably 10° C., more preferably 20° C., even more preferably 30° C., even more preferably 40° C., particularly preferably 50° C., and most preferably 55° C. The upper limit of the reaction temperature is preferably 100° C., more preferably 70° C., and even more preferably 65° C. By setting the reaction temperature within the above range, the yield of the polycondensate can be improved.

[0054] The lower limit of the reaction time is preferably 1 hour, more preferably 5 hours, further preferably 10 hours, and even more preferably 13 hours. The upper limit of the reaction time is preferably 100 hours, more preferably 50 hours, and further preferably 20 hours.

[0055] In this step, it is preferable not to use a catalyst. In particular, it is preferable not to use a catalyst that is commonly used in the synthesis of polyurethane. Although it is not intended to be limiting, if such a catalyst is used, the catalyst may be added to the reactants and prevent the reaction from proceeding beyond a certain level, or conversely, side reactions may be allowed to proceed too far, resulting in an imbalance of the reactants.

[0056] [Precipitation process] In this step, the reaction product obtained in the reaction step is put into water. In this step, the product is precipitated, and the polycondensate can be obtained. Although it is not intended to be interpreted in a limiting manner, water is present in the vicinity of the urethane bond of the polycondensate in this step, and as a result, 1 When the peak integral value in the chemical shift range of 2.30 to 2.55 ppm in the H-NMR spectrum is taken as 1, the peak integral value in the chemical shift range of 3.10 to 3.20 ppm is considered to be more than 2.0.

[0057] The product obtained by precipitation in this step can be purified as necessary to increase the purity of the polycondensate. The product obtained in this step may contain unreacted aliphatic diisocyanate and unreacted betulin as impurities, and it is preferable to perform a purification operation to remove these. EXAMPLES

[0058] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples.

[0059] <Synthesis of polycondensation product> [No.1] 0.4557 parts by mass of betulin was put into a 50 mL flask containing a magnet stirrer, and nitrogen substitution (purity 99.995%) was performed. Then, under a nitrogen atmosphere, 3.5568 parts by mass of tetrahydrofuran (THF) as a solvent was added with a syringe and stirred at room temperature to dissolve betulin (betulin concentration 257 mM). Next, 0.2020 parts by mass of 1,8-diisocyanate octane (molar ratio to betulin 1.0) was weighed with a microsyringe under nitrogen, added to the flask, and dissolved uniformly at room temperature. Then, the flask was immersed in an oil bath previously heated to 60 ° C. to start the polycondensation reaction. The reaction was continued with stirring at 60 ° C. for 15 hours. After the reaction was completed, the reactant was put into 200 mL of high-purity purified water, and the product (first) was precipitated. This product (1) was filtered and separated using a glass filter (1G4), and then the product (1) was added to 200 ml of a mixed solution of high-purity ethanol (Wako Pure Chemical Industries, HPLC-grade high-purity ethanol 99.5% or higher): high-purity purified water = 138:62 by volume ratio to precipitate the product (2), and this product (2) was filtered and separated using a glass filter (1G4). ​​The product (2) was further washed with 30 mL of a mixed solution of high-purity ethanol: high-purity purified water = 138:62 by volume ratio, and then the product (2) was added to 200 ml of high-purity ethanol and filtered using a glass filter (1G4) to obtain a filtrate. The obtained filtrate was concentrated using a rotary evaporator to obtain a product (3). The product (3) was then left to dry for 24 hours in a 40°C vacuum dryer to obtain a polycondensate (A-1). The polycondensate (A-1) was a white powder, and the recovery amount was 0.3379 g, which was a recovery rate of 54.5%. The molecular weight distribution of the polycondensate (A-1) was measured by GPC, and it was found that the Mw was 6,526, the Mn was 1,695, and the Mw / Mn was 3.85, indicating that the polycondensate (A-1) was a polymer.

[0060] [No.2~21] Polycondensates were synthesized in the same manner as in No. 1, except that the type and amount of aliphatic diisocyanate used (molar ratio to betulin), reaction temperature, reaction time, betulin concentration in THF, and catalyst were as shown in Table 1 below. Polycondensates could be obtained for Nos. 2 to 8 and 10 to 17. On the other hand, polycondensates could not be recovered for Nos. 9 and 18 to 21.

[0061] In No. 9, gelation occurred during the reaction, so no polycondensation product could be obtained. In No. 18 and No. 20, the reaction did not proceed, so no polycondensation product could be obtained. In No. 19, the reactants did not dissolve uniformly, so no polycondensation product could be obtained. In No. 21, the amount of polycondensation product produced was so small that it was not possible to recover the polycondensation product.

[0062] The yield, Mw and Mw / Mn of the obtained polycondensates are also shown in Table 1. In Table 1, "-" in the "Catalyst" column indicates that no catalyst was used, "-" in the "Yield (%)" column indicates that the polycondensate could not be recovered, and "-" in the "Mw" and "Mw / Mn" columns indicates that "Mw" and "Mw / Mn" were not measured.

[0063] [Table 1]

[0064] <Confirmation of the structure of polycondensation product (1)> Among the obtained polycondensates, the structures of polycondensates (A-1) and (A-15) to (A-17) were determined by IR and 1 The measurement was performed by H-NMR. IR was measured by a Fourier transform infrared spectrophotometer ("FT / IR-380" manufactured by JASCO Corporation). 1 H-NMR was measured using a nuclear magnetic resonance apparatus (JNM-ECX400 manufactured by JEOL Ltd.) (solvent: CDCl3, internal standard: tetramethylsilane).

[0065] The IR measurement charts of the polycondensates (A-1) and (A-15) to (A-17) are shown in Figures 1 to 4. 1 The H-NMR measurement charts are shown in Figures 5 to 8, respectively.

[0066] In Figures 1 to 4, the urethane bond is characterized by a peak at 3000 cm -1 (NH stretching vibration), 1690 cm -1 (urethane group) and 1510cm -1 Strong peaks were observed in the vicinity of the amide portion of the urethane group.

[0067] From Fig. 5, it was confirmed that the polycondensate (A-1) has a structure in which betulin and 1,8-diisocyanatooctane are stoichiometrically bonded at 1:1. The basis for this is that, in the case of a structure in which betulin is stoichiometrically bonded at 1:1, the attribution of each proton (hydrogen atom) of two hydrogens of the isopropenyl group derived from betulin (No. 30, 4.5-5.0 ppm), hydrogen bonded to the carbon next to oxygen (No. 3, 4.5-5.0 ppm), hydrogen bonded to the carbon next to oxygen (No. 28, 4.1-4.47 ppm and around 3.6-4.0 ppm), and hydrogen attached to the carbon to which the isopropenyl group is bonded (No. 19, 2.3-2.6 ppm) could be quantitatively performed. On the other hand, it was confirmed that the polycondensate (A-1) had a peak integral value of 4.4 at 3.10 to 3.20 ppm (hereinafter also referred to as "around 3.15 ppm"), which was 2.4 larger than the stoichiometric theoretical peak integral value of 2.0.

[0068] From FIG. 6, it was confirmed that the polymer (A-15) differs from the polycondensate (A-1) in that it does not have a structure in which betulin and 1,4-diisocyanatebutane are stoichiometrically bonded in a 1:1 ratio, but has a structure in which a large number of by-products are mixed in.

[0069] From FIG. 7, it was confirmed that, like the polycondensation polymer (A-1), the polycondensation polymer (A-16) has a structure in which betulin and 1,6-diisocyanatehexane are stoichiometrically bonded in a 1:1 ratio, but the peak integral value at about 3.15 ppm is 4.7, which is 2.7 larger than the stoichiometric theoretical peak integral value of 2.0.

[0070] From FIG. 8, it was confirmed that, like the polycondensation polymer (A-1), the polycondensation polymer (A-17) has a structure in which betulin and 1,12-diisocyanate dodecane are stoichiometrically bonded in a 1:1 ratio, but the peak integral value near 3.15 ppm is 4.5, which is 2.5 larger than the stoichiometric theoretical peak integral value of 2.0.

[0071] <Confirmation of the structure of polycondensation product (2)> Regarding the polycondensates (A-1), (A-16) and (A-17), 1 The peak integral value around 3.15 ppm in H-NMR was larger than the stoichiometric theoretical value (2.0), possibly due to the presence of water in the polycondensate, so a differential scanning calorimeter (Texas Instruments' "DSC-25") was used to examine whether or not there was a glass transition point of water. The measurement conditions were as follows: the temperature was lowered from room temperature (20°C) to -90°C at a rate of 5°C / min, held for 5 minutes, and then raised to 20°C at a rate of 5°C / min.

[0072] The DSC results of the polycondensates (A-1), (A-16) and (A-17) are shown in Figures 9 to 14. Figures 10, 12 and 14 show enlarged views of the vicinity of -50°C in Figures 9, 11 and 13, respectively.

[0073] According to a literature (Bull. Chem. Soc. Japan 41, 2591 (1968)), there are three types of water surrounding polymers: (1) water that cannot be detected as a first-order phase transition (so-called non-freezing water), (2) water with a structure different from pure water observed at around -45°C, and (3) free water observed at around -20°C. It is known that the water (non-freezing water) in the above-mentioned (1) exhibits a clear glass transition at a temperature lower than around -55°C, which is higher than the glass transition point of water, which is -138°C, and moves depending on the type of sample and the moisture content. From Figures 9 to 14, the glass transition points of the polycondensates (A-1), (A-16) and (A-17) are all slightly higher than the temperature in the vicinity of -55°C, and are higher (around -50°C) than the glass transition point of water (-138°C, literature value), and therefore it is considered to be water different from free water (the above-mentioned water in (2)).

[0074] <Confirmation of the structure of polycondensation product (3)> The polycondensate (A-1) was analyzed by thermobalance-mass spectrometry (TG-MS) to determine compounds generated upon heating. The results are shown in FIG.

[0075] 15, it was found that the substance (water) derived from Mw=18 was gradually generated from around 200° C. From this result, it is considered that the water present in the vicinity of the polycondensate remains in a relatively stable state.

[0076] From the above results, 1 The reason why the peak integral value of 3.10 to 3.20 ppm in H-NMR is larger than the stoichiometric theoretical peak integral value of 2.0 is strongly suggested to be that water other than free water exists near the polycondensate. It is presumed that water other than free water exists near the polycondensate by pouring the reaction mixture into water after the polycondensation reaction is completed and precipitating it.

[0077] <Thermal properties of polycondensates> For the polycondensates (A-1), (A-16) and (A-17), several mg of each white powder was placed in an aluminum pan for measurement, and the differential scanning calorimeter was used to heat the polycondensates from 40°C to 200°C at a heating rate of 10°C / min, and then cooled to 40°C at a heating rate of 10°C / min, and then heated again from 40°C to 200°C at a heating rate of 10°C / min, to examine the thermal properties of each polycondensate. The DSC results of the polycondensates (A-1), (A-16) and (A-17) are shown in Figures 16 to 18.

[0078] 16 to 18, it was found that each polycondensate had a glass transition point between 95 and 127°C after the second heating. It was also found that the glass transition point shifted to the lower temperature side as the number of methylene groups (-CH2-) increased, and that there was a negative correlation between the number of methylene groups and temperature.

[0079] <Mechanical properties of molded products> When a small amount (100-200 mg) of the white powder of the polycondensate (A-1) was placed on a hot plate with a surface temperature of 190°C, the polycondensate became soft and could be molded into the desired shape with a spatula or the like. The mixture was stirred for about 15 minutes to remove the gas (air) contained therein, and finally a small piece was prepared, from which a molded body (length 6.73 mm x width 17.1 mm x thickness 1.17 mm) was cut out. The surface area of ​​the obtained molded body was measured using an image analyzer (Hirox Co., Ltd.'s "KH-8700"), and the density was calculated from the surface area, thickness, and mass. Next, the mechanical properties of the molded body were examined using a viscoelasticity measuring device (Texas Instruments' "RSA-D2") at a heating rate of 10°C / min in the range of -50°C to 100°C.

[0080] As a result, the flexural modulus E' showed stable values ​​in the range of -50°C to 100°C, the specific modulus at room temperature (20.5°C) was 14145.5Nm / kg, and the loss tangent (Tan δ) was 0.029. The measurement results of the specific modulus are shown in FIG. 19, and the measurement results of the loss tangent are shown in FIG. 20. Note that FIG. 19 and FIG. 20 show the measurement results of the polycondensate (A-1) at room temperature (20.5°C) and at 100.0°C, and the literature value of the rigid polyurethane foam as a control (the specific modulus is the value described in Materials Construction (2015), Architectural Institute of Japan, September 2015, 959-960 converted from the unit, and the loss tangent is the value described in Polymer Journal, Vol. 57, No. 9, 552-560 (Sep., 2000)).

[0081] From Figs. 19 and 20, it was found that the specific elastic modulus is a low value compared to that of a general rigid polyurethane foam, and the loss tangent (Tan δ) also shows a low value at room temperature (20.5°C), which is a practical temperature, and that the material is positioned in a new area as a polyurethane material and is a material that can be expected to be applied in various fields. In particular, it can be seen that the specific elastic modulus of the molded body does not change significantly between 20.5°C and 100.0°C, but the loss tangent is significantly different between 20.5°C and 100.0°C, and is significantly increased at 100.0°C compared to 20.5°C. Such a specific change in the loss tangent is a physical property not seen in conventional polyurethane foams. For example, International Publication No. 2013 / 108582 describes a polyurethane foam whose loss tangent decreases as the temperature increases from 20°C to 100°C. It is believed that such a specific change in the loss tangent, that is, the large increase in the loss tangent when the temperature increases from 20.5°C to 100.0°C, is due to water present in the vicinity of the polycondensate. In addition, the material used as the diaphragm, such as cone paper (with a specific elastic modulus of approximately 6×10 6 Since this material has a low specific elastic modulus and a high loss tangent (Tan δ) compared to other materials (such as silicon dioxide, which has a loss tangent of approximately 0.05), it is believed to be useful as a broadband soft material that suppresses split vibrations.

[0082] <Reference example> In Example 4 of JP-A-2001-105482, it is described that betulin polyurethane was produced from betulin and 1,6-diisocyanate hexane. In Example 4, the product was not precipitated by pouring into water after the polycondensation reaction was completed, so it is considered that water does not exist near the obtained betulin polyurethane. In order to confirm this point, we attempted to synthesize betulin polyurethane in the same manner as in Example 4 of JP-A-2001-105482. Specifically, a stirrer and 400 milligrams (0.915 mmol) of betulin were placed in a 500 ml reaction vessel equipped with a cooling tube and a septum cap, and the inside of the reaction vessel was replaced with nitrogen of 99.995% purity. Then, 185 milligrams (1.1 mmol) of hexamethylene diisocyanate was poured into the vessel using a microsyringe. The hexamethylene diisocyanate was only partially absorbed by the powder of betulin, and was not mixed uniformly even when stirred with a stirrer. Next, heating was attempted in a hot water bath at a temperature of 50°C, but no change was observed. Moreover, over time, the mixture became a solid, non-uniform mass, was not mixed uniformly, and the polycondensation reaction did not proceed. The reproducibility of Example 4 of JP 2001-105482 A could not be confirmed. In addition, since there is no description of the recovery amount or yield of betulin polyurethane in Example 4 of JP-A-2001-105482, the possibility that an extremely small amount of betulin polyurethane was produced cannot be denied. In addition, although Example 4 of JP-A-2001-105482 describes the number of millimoles of betulin as 1 millimole, the molecular weight of betulin is 442.72 g / mol, so the correct number is about 0.915 mmol.

Claims

1. A polycondensation product of betulin and an aliphatic diisocyanate, 1 A polycondensate having a peak integral value of more than 2.0 in a chemical shift range of 3.10 to 3.20 ppm when the peak integral value in a chemical shift range of 2.30 to 2.55 ppm in a H-NMR spectrum is taken as 1.

2. The polycondensate according to claim 1, wherein the peak integral value in the chemical shift range of 3.10 to 3.20 ppm is 3.0 or more and 5.0 or less.

3. 2. The polycondensate according to claim 1, having a weight average molecular weight of 3,000 or more and 30,000 or less.

4. 2. The polycondensate according to claim 1, having a dispersity of 1.0 or more and 6.0 or less.

5. 2. The polycondensate according to claim 1, wherein the aliphatic diisocyanate has 6 to 12 carbon atoms excluding the isocyanate group.

Citation Information

Patent Citations

  • Polymer obtained from betulin and its production method

    JP2001288222A